Respuesta :
y+3 = (2/3)(x+6)
y+3 = (2/3)(x) + 4
y = (2/3)(x) + 1
y=2/3x + 1 Subtract (2/3x) from both sides y-2/3x=1
Rearrange -------- -2/3x + y = 1
Multiple both sides by 3 ---- (3)((-2/3)x + y) = 1
Distribute the 3 ---- -6/2x + 3y = 3 -> -2x+3y=3
Standard Form = -2x+3y=3
y+3 = (2/3)(x) + 4
y = (2/3)(x) + 1
y=2/3x + 1 Subtract (2/3x) from both sides y-2/3x=1
Rearrange -------- -2/3x + y = 1
Multiple both sides by 3 ---- (3)((-2/3)x + y) = 1
Distribute the 3 ---- -6/2x + 3y = 3 -> -2x+3y=3
Standard Form = -2x+3y=3